Faktor-Faktor yang Mempengaruhi Pemahaman Pelaku UMKM dalam Menyusun Laporan Keuangan Berdasarkan SAK EMKM di Kelurahan Kota Uneng - Apolonia Septiana Embu; Henrikus Herdi; Paulus Libu Lamawitak (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The aim of this research is to determine the influence of educational background, socialization of SAK EMKM and business scale on the understanding of MSME actors in Uneng City Subdistrict in preparing financial reports based on SAK EMKM. Effective socialization of SAK EMKM is an important key in improving the quality of MSME financial reports. The data used in this research is primary data, where primary data collection was carried out by distributing questionnaires to MSME owners and the data analysis technique used used a Likert scale. The population in this research is MSMEs which only operate in the trade sector in Uneng City Village, Sikka Regency, as many as 176 MSME actors and the sampling technique uses the Slovin formula, namely 64 respondents. The data analysis method uses multiple linear regression analysis with the help of the SPSS Statistics version 22 program. The results of this research state that the variables of educational background, socialization of SAK EMKM and business scale partially and simultaneously have a significant effect on the understanding of MSME actors in preparing financial reports based on SAK EMKM.